math science

posted by .

How do you solve (1+tanX)/(sinX)using identities?
I got cscX

  • math science -

    Hmmm.

    1/sinx= cscx

    so what happened to 1+tanx?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Mathematics - Trigonometric Identities

    Prove: sinx + tanx = tanx (1 + cosx) What I have so far: LS: = sinx + tanx = sinx + (sinx / cosx) = (sinx) (cosx) + sinx / cos = tanx (cosx + sinx) I don't know what to do now
  2. drwls

    My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to …
  3. Pre-Calculus

    Find a numerical value of one trigonometric function of x if tanx/cotx - secx/cosx = 2/cscx a) cscx=1 b) sinx=-1/2 c)cscx=-1 d)sinx=1/2
  4. Math

    Solving Identities [(1+tanx)/(sinx)]- secx I got cscx please halp me to solve it to see if its right
  5. trig

    We are doing trig identities in school. I need help with these five: 1.1+sinx/1-sinx=cscx+1/cscx-1 2.tanx+sinx/1+cosx=tanx 3.sec^2x/sin^2x=1/sin^2x+1/cos^2x 4.tan^2x/1+tan^2x=1-cos^2x 5.sinx-sin^3x/cos^3x=tanx
  6. Trig Help

    Prove the following: [1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx] =[1+sinx]/[(sinx+1)/sinx] =[1+sinx]*[sinx/(sinx+1)] =[sinx+sin^2x]/[sinx+1] =[sinx+(1-cos^2x)]/[sinx+1] =?
  7. Math

    Im really struggling with these proving identities problems can somebody please show me how to do these?
  8. Math

    Im really struggling with these proving identities problems can somebody please show me how to do these?
  9. Math please help quick

    Which of the following are identities? Check all that apply. (Points : 2) sin2x = 1 - cos2x sin2x - cos2x = 1 tan2x = 1 + sec2x cot2x = csc2x - 1 Question 4. 4. Which of the following equations are identities?
  10. Precalculus/Trig

    I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't know …

More Similar Questions